Linguistic insecurity and professional identity: Mainland Chinese pre-service English teachers navigating NNEST identity in Hong Kong - Chan, Ka Long; Liu, Jinyu (Journal of Interdisciplinary Studies in Education, 2026)
Non-native English-speaking teachers' (NNESTs) identity has long been a research topic among scholars in the teacher education field. The study of NNESTs' identity is critical to the future design and implementation of teacher education and policy. With the rise of the Top Pass Talent Scheme, there is expected to be an increase in NNESTs from mainland to Hong Kong, which has not attracted a lot of attention in terms of research and resources. By thematically analyzing the interview data from 14 pre-service teachers, this study aims to investigate how native speakers interact with the NNEST identity among the pre-service teachers from the mainland. The results showed that NNESTs displayed linguistic insecurity and professional insecurity.